2003
DOI: 10.1086/379508
|View full text |Cite
|
Sign up to set email alerts
|

The Ionized Gas and Nuclear Environment in NGC 3783. IV. Variability and Modeling of the 900 KilosecondChandraSpectrum

Abstract: We present a detailed spectral analysis of the data obtained from NGC 3783 during the period 2000-2001 using Chandra. The data were split in various ways to look for time-and luminosity-dependent spectral variations. This analysis, along with the measured equivalent widths of a large number of X-ray lines and photoionization calculations, lead us to the following results and conclusions. 1) NGC 3783 fluctuated in luminosity by a factor ∼ 1.5 during individual observations (most of which were of 170 ks durati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
308
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(348 citation statements)
references
References 33 publications
37
308
2
1
Order By: Relevance
“…Multi-waveband campaigns A&A 589, A76 (2016) provided the detailed broad-band spectrum and the timedependent behavior of X-ray outflows in a number of bright Seyfert-1 galaxies: NGC 7469 , NGC 5548 Kaastra et al 2004;Steenbrugge et al 2005), Mrk 509 Steenbrugge et al 2011;Kaastra et al 2011Kaastra et al , 2012Ebrero et al 2011;Arav et al 2012), IRAS 13449+2438 (Lee et al 2013;Di Gesu et al 2013, NGC 3783 (Kaspi et al 2002;Gabel et al 2003;Netzer et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Multi-waveband campaigns A&A 589, A76 (2016) provided the detailed broad-band spectrum and the timedependent behavior of X-ray outflows in a number of bright Seyfert-1 galaxies: NGC 7469 , NGC 5548 Kaastra et al 2004;Steenbrugge et al 2005), Mrk 509 Steenbrugge et al 2011;Kaastra et al 2011Kaastra et al , 2012Ebrero et al 2011;Arav et al 2012), IRAS 13449+2438 (Lee et al 2013;Di Gesu et al 2013, NGC 3783 (Kaspi et al 2002;Gabel et al 2003;Netzer et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more and more observations showed that the K-shell lines, namely 1s−2p transitions, from these low-ionization ions of Si can also be found in high-resolution X-ray spectra. Kaspi et al (2002) and Netzer et al (2003) detected the Si vii to Si xiv K lines in spiral galaxy Full Tables 3 and 4 are only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/566/A105 NGC 3783. Holczer et al (2010) reported Si vi to Si xiv absorption lines in the slow warm absorber of bright Seyfert 1 galaxy MCG 6-30-15.…”
Section: Introductionmentioning
confidence: 99%
“…There are several sources for which the variability approach has been successful, but all have difficulties or large changes in flux. The Chandra data of NGC 3783 (Netzer et al 2003;Krongold et al 2005) were spread out over several months (with distance limits between 0.2 and 25 pc), while the XMM-Newton observations of this source ) occurred during a gradual rising phase without clear flux extrema, with no changes in the absorber properties leading to a minimum distance of 0.5-2 pc from the source, depending on the ionization component. In NGC 4051 the flux dropped by a factor of five (Steenbrugge et al 2009) leading to a 0.02-1 pc upper limit on the location of the absorbing gas.…”
Section: Introductionmentioning
confidence: 99%